Prevalence and associated factors of diabetic ketoacidosis among patients with diabetes mellitus at the University of Gondar Comprehensive and Specialized Referral Hospital Northwest, Ethiopia. - Abebe Birhanu; Sintayehu Ambachew; Netsanet Baye; Emiyamrew Getnet; Sintayehu Admas; Eshet Gebrie; Abebaw Worede (PLoS ONE)
Background Diabetes is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. Diabetic ketoacidosis is one of the life-threatening complications in diabetic individuals with, high morbidity and mortality globally. However, the data related to the prevalence and associated factors of diabetic ketoacidosis are limited in the study setting. Objective To assess the prevalence of diabetic ketoacidosis and its associated factors among diabetic mellitus patients at the University of Gondar Comprehensive Specialized Hospital. Methods A hospital-based cross-sectional study was conducted from March 1 to September 30, 2021. A total of 405 diabetic patients aged 20 and above were selected using a systematic random sampling technique. A total of 810 blood and urine samples (each 405) were collected using sterile serum separator tubes and urine collection cups, respectively. Sociodemographic and clinical data was collected using a structured questionnaire. Chemical analysis of urine was done using urine reagent strips to determine urine ketone bodies and PH. BECKMAN COULTER DxC700 AU clinical chemistry analyzer instrument was used to determine electrolytes and metabolites. The data was entered using Epi-Data version 4.6 and transferred to SPSS version 25 for analysis. Bivariable and multivariable logistic regression analyses were used to determine the factors associated with the diabetic ketoacidosis. The results were considered statistically significant if the adjusted odds ratio was reported with a 95% confidence interval and a P-value below 0.05. Results The overall prevalence of diabetic ketoacidosis among diabetic patients was 35/405 (8.6%, 95% CI: 6.0-11.0%). Of these cases, 25 (71.4%) had type 1 diabetes mellitus, while 10 (28.6%) had type 2 diabetes mellitus. Statistically significant factors associated with diabetic ketoacidosis included being a young adult aged 20-29 years (AOR = 2.262; 95% CI = 1.090-4.758; P = 0.013), unemployment (AOR = 2.578; 95% CI = 1.457-6.113; P = 0.017), the presence of infection (AOR = 2.819; 95% CI = 1.138-8.428; P = 0.024), and being T1DM (AOR = 3.106; 95% CI = 1.150-7.273; P = 0.003). Conclusions and recommendations The prevalence of diabetic ketoacidosis among follow-up diabetes patients in this study was high, particularly among those aged 20-29 years, unemployed, or with infections. Increased vigilance, regular monitoring, timely infection management, and comprehensive diabetes education are essential for early detection and prevention of DKA. Social and financial support for unemployed diabetic patients can further enhance access to care and reduce DKA risk.